2009
DOI: 10.1063/1.3238567
|View full text |Cite
|
Sign up to set email alerts
|

Dual folding pathways of an α/β protein from all-atom ab initio folding simulations

Abstract: Successful ab initio folding of proteins with both ␣-helix and ␤-sheet requires a delicate balance among a variety of forces in the simulation model, which may explain that the successful folding of any ␣ / ␤ proteins to within experimental error has yet to be reported. Here we demonstrate that it is an achievable goal to fold ␣ / ␤ proteins with a force field emphasizing the balance between the two major secondary structures. Using our newly developed force field, we conducted extensive ab initio folding simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 44 publications
5
27
0
Order By: Relevance
“…The folding mechanisms reproduced in the present study were consistent with the results from the preceding studies. For FSD‐EY, the microsecond‐order replica exchange MD simulations with the explicit solvent model have reported the two folding pathways that were consistent with our results from the implicit solvent model, that is, (1) the α‐helix part folded first and followed by the folding of the β‐sheet, and (2) formation of the β‐sheet preceded that of the α‐helix. For a total simulation time, this preceding study required 4.8 μs in total (240 ns with 20 replicas).…”
Section: Resultssupporting
confidence: 85%
“…The folding mechanisms reproduced in the present study were consistent with the results from the preceding studies. For FSD‐EY, the microsecond‐order replica exchange MD simulations with the explicit solvent model have reported the two folding pathways that were consistent with our results from the implicit solvent model, that is, (1) the α‐helix part folded first and followed by the folding of the β‐sheet, and (2) formation of the β‐sheet preceded that of the α‐helix. For a total simulation time, this preceding study required 4.8 μs in total (240 ns with 20 replicas).…”
Section: Resultssupporting
confidence: 85%
“…Therefore, we decided to reparameterize the force field under the same solvation scheme (GB/SA) for a better balance of the two major secondary structures. Using the newly developed force field, we conducted ab initio folding of FSD with both CMD and REMD (Lei, Wang et al 2009). High accuracy folding was achieved in terms of both the best folded structure (0.8 Å RMSD) and the population of the folded conformation (64.2%).…”
Section: Fig 7 Structure Of Albumin Binding Domain (Abd)mentioning
confidence: 99%
“…[5][6][7][8][9] In some of the implicit water simulation studies, the backbone energy term in the amber ff99 force field were re-parameterized to improve the propensity of the secondary structures. 5,6 Recently, it was found that even without re-optimization, a combination of standard amber ff96 with GB implicit solvation models produce a reliable free energy landscape for 1FSD folding.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this pathway is consistent with a previously suggested pathway from allatom simulations with a GB implicit solvation model. [5][6][7] The other folding pathway (Path II), which is rather new, suggested the simultaneous formation of the secondary structural elements (α and β segments) and the hydrophobic tertiary core (U2→T2→N).…”
mentioning
confidence: 99%